Cerebral cavernous malformations associated to meningioma: High penetrance in a novel family mutated in the PDCD10 gene - Garaci, Francesco; Marsili, Luisa; Riant, Florence; Marziali, Simone; Cécillon, Michaelle; Pasquarelli, Roberto; Sangiuolo, Federica; Floris, Roberto; Novelli, Giuseppe; Tournier-Lasserve, Elisabeth; Brancati, Francesco (The neuroradiology journal, 2015)
Multiple familial meningiomas occur in rare genetic syndromes, particularly neurofibromatosis type 2. The association of meningiomas and cerebral cavernous malformations (CCMs) has been reported in few patients in the medical literature. The purpose of our study is to corroborate a preferential association of CCMs and multiple meningiomas in subjects harbouring mutations in the PDCD10 gene (also known as CCM3). Three members of an Italian family affected by seizures underwent conventional brain Magnetic Resonance Imaging (MRI) with gadolinium contrast agent including gradient echo (GRE) imaging. The three CCM-causative genes were sequenced by Sanger method. Literature data reporting patients with coexistence of CCMs and meningiomas were reviewed. MRI demonstrated dural-based meningioma-like lesions associated to multiple parenchymal CCMs in all affected individuals. A disease-causative mutation in the PDCD10 gene (p.Gln112PhefsX13) was identified. Based on neuroradiological and molecular data as well as on literature review, we outline a consistent association between PDCD10 mutations and a syndrome of CCMs with multiple meningiomas. This condition should be considered in the differential diagnosis of multiple/familial meningioma syndromes. In case of multiple/familial meningioma the use of appropriate MRI technique may include GRE and/or susceptibility-weighted imaging (SWI) to rule out CCM. By contrast, proper post-gadolinium scans may aid defining dural lesions in CCM patients and are indicated in PDCD10-mutated individuals.